Synthetic Approaches to New Antimicrobial Active Natural Products - Semmler, Sandra; Justus Liebig University Giessen (My University, 2022)
Natural products (NPs) present great chances to identify novel antimicrobial active substances with unprecedented structures. Synthetic access to natural derived compounds is essential in the development process of new drugs. However, usually scarcity of isolated material makes complete activity profiling difficult. Hence, there is the need for synthetic routes to acquire not just the natural product itself, but rather derivatives for the development of in-depth structure-activity relationship (SAR) studies for future drug development. Peptide-based NPs with a molecular weight between “small drugs” and “biologics” are still an underexplored type of NPs, which have the potential to combine the advantage of high selectivity and bioavailability. Chapter 1 – The known natural product Globomycin (GLM) is a cyclic peptide that shows activity against Gram-negative bacteria (MIC of 6.25 μg/mL for E. coli SANK 70569)29. After identifying an in-house producer strain, molecular network analysis of extracts derived from Streptomyces sp. HAG010519 revealed a total of 29 natural derivatives of GLM. For eleven derivatives a structural proposal based on MS/MS data has been given. Early ADME (Absorption, distribution, metabolism, excretion) tests were performed and revealed a high metabolic liability of GLM. To address this issue, a rational design approach to develop more stable derivatives was performed. Therefore, structure-based drug design (SBDD) and molecular docking studies were applied to focus the synthesis on the most promising derivatives. A solid-phase peptide synthesis (SPPS) approach was developed, with a macrolactamization between amino acids 5 and 4 (Figure 4-7) for the ring closure. The newly developed synthetic route has overall fewer synthetic steps, a high stereoselectivity for the fatty acid side chain, and gives a two-step procedure to introduce more extraordinary amino acid building blocks like hydroxyprolines. The four successfully synthesized derivatives show noticeable activity against the tested E. coli strains, with the highest one of 16 μg/mL, and that the docking scores delivered a good assessment between the compounds. Chapter 2 – Falcitidin is an inhibitor of cysteine protease falcipain-2. Molecular network revealed over30 natural analogs of falcitidin. Total synthesis of chosen analogs was achieved using a SPPS approach followed by functional group interconversion of the cleaved peptide acid to the alcohol, followed by Dess-Martin oxidation to the aldehyde. Thereby, access to functionalized pentapeptides was established. In vitro testing against selected proteases, as well as falcipain-2 and -3 showed superior inhibitory activity than falcitidin itself. Chapter 3 – In extracts of Pedobacter cryoconitis linear peptides containing dehydro amino acids were detected by metabolomics analyses. The compounds were called cryopeptides and contain two dehydrogenated valines in their structure. This feature can be found in other NPs as well. However, the biochemical basis of this dehydrogenation process of amino acids is not reported yet. To enable further studies in this direction and to investigate which substrate is used, precursor molecules were successfully synthesized. Furthermore, a synthetic route to two Cryopeptides and to two non-natural derivatives was developed for full structure elucidation,activity testing of the molecules and future enzymatic assays.
Keywords: Chemistry; ddc:570; ddc:630